Computational Intelligence 9th International Joint Conference, IJCCI 2017 Funchal-Madeira, Portugal, November 1-3, 2017 Revised Selected Papers - Sabourin, Christophe; Merelo, Juan Julian; Madani, Kurosh; Warwick, Kevin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents revised and extended versions of the best papers presented at the 9th International Joint Conference on Computational Intelligence (IJCCI 2017), held in Funchal, Madeira, from 1 to 3 November 2017. It focuses on four of the main fields of computational intelligence: evolutionary computation, fuzzy computation, neural computation, and cognitive and hybrid systems. As well as presenting the recent advances of these areas, it provides new and innovative solutions for established researchers and a source of information and/or inspiration those new to the field. Discussing innovative techniques in various application areas, it is a useful resource for individual researchers and a valuable addition to academic libraries (of universities and engineering schools).
Particle Stability Time in the Stochastic Model of PSO -- Optimizing Costs and Quality of Interior Lighting by Genetic Algorithm -- Mining of Keystroke and Mouse Dynamics to Increase the Engagement of Students with Programming Assignments.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence